High Temperature Oxidized SnO2 Films Prepared by Reactive Sputtering - G. Beensh-Marchwicka; L. Król-Stępniewska; A. Misiuk (Active and Passive Electronic Components)
Undoped and Sb-doped tin oxide films were prepared by d.c. reactive ion sputtering in an argon atmosphere with oxygen partial pressures ranging from 0 to 50%. The films were anneled in oxygen in the temperature range 360 - 893℃. The effect of thermal annealing on the changes in electrical and structural properties is described.